Gram-Negative Bacilli in Critically Ill Burn Patients. (4th October 2017) - Williams, Shannon; Miller, Melissa; Van Duin, David; Carson, Shannon; Cairns, Bruce; Lachiewicz, Anne
Abstract: Background: Among critically ill burn patients, the ability of surveillance screening to predict clinical gram-negative bacilli (GNB) infections is unknown. In this study, isolates identified by surveillance screening using vancomycin-amphotericin-ceftazidime-clindamycin (VACC) agars are compared with clinical isolates. Methods: Consented adult ICU patients with ≥20% burn or inhalation injury were screened from admission until ICU discharge (range, 1–29 weeks) with once weekly wound and perirectal swabs and twice weekly tracheal aspirates if intubated. Surveillance samples were incubated overnight in tryptic soy broth and inoculated to VACC agar. VACC agars select for extended-spectrum β-lactamase producing- Enterobacteriaceae but allow breakthrough of glucose nonfermenting GNB. GNB isolated in 48 hours were identified and tested for antibiotic resistance using Kirby–Bauer methods with CLSI breakpoints. Clinical cultures were tested by routine methods in the clinical laboratory. Results: Of 654 screened patients, 66 were eligible and 52 enrolled (Figure 1). Ninety percent consented to screening with 62% screened at all 3 sites. 450 GNB isolates were obtained from 1, 059 surveillance samples. 119 clinical GNB isolates were obtained. P . A eruginosa composed 40% of surveillance and 34% of clinical isolates. Figure 2 shows the wide variety of GNB that were detected. Thirty-one percent of GNB clinical isolates were multidrug-resistant (MDR) (Table 1). Conclusion: These unique data highlight the high burden of GNB and MDR-GNB among burn patients. Screening detected a wider variety of GNB species than clinical culture alone especially in wounds. Disclosures: D. Van Duin, Astellas: Scientific Advisor, Consulting fee. Achaogen: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. MedImmune: Scientific Advisor, Consulting fee. Shionogi: Scientific Advisor, Consulting fee.